Yadava - A Pastoral Caste of Kerala - M.S. Mahendrakumar (Anthropologist, 8(2): 83-87 (2006), 2006)
The Yadava of Kannur district in Kerala is a caste group engaged in cattle-rearing traditionally. They are believed to have migrated from Andhra Pradesh before Independence. The Yadavas came and settled in certain towns, suburbs and townships in the erstwhile Malabar, i.e., in the Northern Kerala. Yadavas are concentrated in Kannur town, Koothuparamba, Thazhe Chovva, and in Calicut town. Most of the families are rearing buffaloes and selling milk. Continuous cultural contacts and various other factors like education, industries, and employment opportunities within the towns and outside paved the way for socio-cultural change. The traditional subsistence activities of the Yadavas are declining today. An attempt is made in this article to trace the major reasons for social and cultural change. The use of three important concepts, namely, acculturation, environmental determinism, and environmental possibilism are examined in the light of the present material